THE EFFECT OF ORANGE SWEET POTATO FLOUR SUBSTITUTION ON THE QUALITY OF ONION CRACKERS - Mariatul Kiptiah; Nina Hairiyah; Hermawan Susanto (Jurnal Agroindustri, 2021)
Sweet potato is a food plant group that is most widely cultivated as an agricultural commodity with carbohydrate sources. The carbohydrate and starch content of orange sweet potato allows the material to be processed into flour and substitutes tapioca flour in the manufacture of garlic cracker products. The purpose of this study was to analyze the physical properties of orange sweet potato flour as a substitute for making onion crackers, determine the best formulation by adding orange sweet potato flour to the onion cracker product, and analyzing the effect of adding orange sweet potato flour to the preference level of panelists for onion cracker products. The research design used in the study consisted of 4 types of formulations with the addition of 0%, 10%, 20% and 30% tapioca flour. Tests carried out on onion crackers substituted for orange sweet potato flour were water content test, ash content test, and organoleptic test. The results showed that the orange sweet potato flour had the characteristics of an orange color, a distinctive aroma of orange sweet potato, and a smooth texture. The best formulation is the addition of orange sweet potato flour as much as 10% (F1) with a moisture content value of 5%, an ash content of 2.3%, and Preferred by panelist (total score 15.56). The addition of orange sweet potato flour to garlic cracker products affected the panelists' preference for color and aroma, but did not affect the taste and texture of onion crackers.